Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/s0950268819002115
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional serosurvey of Coxiella burnetii in healthy cattle and sheep from extensive grazing system in central Italy

Abstract: A cross-sectional survey was carried out to estimate the seroprevalence of Coxiella burnetii in extensively grazed cattle and sheep from central Italy and to identify the related risk factors. Data on notified human Q fever cases in the area were also collected and described. A two-stage cluster sampling was performed. A total of 5083 animals (2210 cattle; 2873 sheep) belonging to 186 farms (92 herds; 94 flocks) were tested for the presence of antibodies against C. burnetii using a commercial enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 44 publications
3
21
1
Order By: Relevance
“…The four flocks were managed under a semiextensive system where animals are housed during lambing and milking and, afterwards, graze on communal mountain pastures in contact with livestock and wildlife. In a region like the Basque Country, where Q fever is endemic and vaccination is not frequently implemented, this system poses a risk for infection and reinfection (14,15,17). Nevertheless, the infection peak observed in yearlings in flock 1 during the second and fourth lambing seasons is difficult to explain since yearlings did not share grazing pastures with other flocks.…”
Section: Discussionmentioning
confidence: 99%
“…The four flocks were managed under a semiextensive system where animals are housed during lambing and milking and, afterwards, graze on communal mountain pastures in contact with livestock and wildlife. In a region like the Basque Country, where Q fever is endemic and vaccination is not frequently implemented, this system poses a risk for infection and reinfection (14,15,17). Nevertheless, the infection peak observed in yearlings in flock 1 during the second and fourth lambing seasons is difficult to explain since yearlings did not share grazing pastures with other flocks.…”
Section: Discussionmentioning
confidence: 99%
“…A review comprising qualitative assessment of 69 publications indicated the detection of C. burnetii infection in all 5 continents (Africa, America, Asia, Europe and Oceania) with wide range of host species and median prevalence of C. burnetii infection among cattle was reported as 20% at the animal level [2]. In a recent cross-sectional serosurvey from Italy on C. burnetii in apparently healthy cattle (n = 2210), the prevalence at the animal-level was observed as 12.0% [17]. Globally, the epidemiology of coxiellosis in water buffaloes (Bubalus bubalis) is largely unknown [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the old animals were found to have higher odds for coxiellosis in univariate as well as multivariable binary logistic regression analysis (Tables 3 and 4). Earlier, the older animals have been reported to have increased odds of getting infected, most often after the first calving [28,30] and increasing of age might be associated with higher probability of being exposed to the pathogen [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations